Nanometer sandwich structure and preparation method and application thereof
By dispersing the nanonuclear material and the nanosheet-like material into different solvents in solution, mixing, quenching and annealing, precise assembly on the nanoscale is achieved, which solves the problem of nanocomposite structure regulation and improves the stability and application potential of the material.
Patent Information
- Application Number
- CN202311350450.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to micro-control the structure and morphology of nanocomposites in solution, resulting in poor stability and easy agglomeration of nanomaterials.
The nanosandwich structure is obtained by dispersing the nanonuclear material and the nanosheet-like material into different solvents, mixing and quenching to form solvent crystals, and precise assembly on the nanoscale is achieved through domain space during the annealing treatment.
The precise assembly of nanomaterials is achieved, the stability and yield of nanocomposites are improved, and it is suitable for systems of a variety of nanomaterials, with better fluidity, fillability and specific surface area.
Smart Images

Figure CN119842097A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a method for preparing a novel nano material, in particular to a nano sandwich structure and a preparation method and application thereof. Background Art
[0002] Nanomaterials have very wide applications in electronics, medicine, environmental protection, energy and other fields due to their excellent physical and chemical properties. However, due to the high surface activity of nanomaterials, single nanomaterials often have poor stability and are prone to agglomeration. Conventional methods for preparing nanocomposites are generally carried out in liquid phase systems, and it is difficult to micro-control the structure and morphology of the composites, and they are prone to random aggregation in solution. Moreover, conventional preparation methods for the synthesis of nanocomposites focus on the design of raw materials and the selection of preparation systems. During the synthesis process, it is still extremely challenging to precisely control the structure of nanomaterials by controlling the conditions of the reaction process. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0004] A method for preparing a nano sandwich structure, the preparation method comprising:
[0005] Step 1: dispersing the nano-core material in a first solvent to obtain a dispersion of the nano-core material, and dispersing the nano-sheet material in a second solvent to obtain a dispersion of the nano-sheet material;
[0006] Step 2: mixing the dispersion of the nano-sheet material and the dispersion of the nano-core material in step 1 to obtain a mixed solution, and quenching to form solvent crystals; the nano-sheet material and the nano-core material are dispersed in the solvent crystals;
[0007] Step 3: Annealing the solvent crystals obtained in step 2 to mature the solvent crystals; at this time, due to the enrichment of the solute at the interface, a confined space is formed on the surface of the solvent crystal, and the nano-sheet material and the nano-core material are dispersed in the confined space, achieving precise assembly on the nanoscale to obtain the nano-sandwich structure.
[0008] According to an embodiment of the present invention, in step 1, in the dispersion of the nanocore material, the concentration of the nanocore material is not specifically limited, as long as the nano sandwich structure can be obtained. Exemplarily, when the nanocore material is selected from metal organic framework nanoparticles or metal organic framework nanosheets, the concentration of the metal organic framework nanoparticles or metal organic framework nanosheets is 0.01-0.1 mg / ml; if the metal organic framework concentration is too high, the yield of the prepared nano sandwich structure will be reduced; if the metal organic framework concentration is too low, the efficiency of preparing the nano sandwich structure is too low.
[0009] According to an embodiment of the present invention, in step 1, the nanocore material is a nanoparticle or a nanosheet structure.
[0010] According to an embodiment of the present invention, the nanocore material is selected from at least one of nanoparticles, nanosheets, molecular sieves, and the like.
[0011] According to an embodiment of the present invention, the size of the nano-core material is not greater than 3 μm, preferably 0.1-3 μm, for example 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm. When the size is greater than 3 μm, the particles or nano-sheets of the nano-core material are easily precipitated.
[0012] According to an embodiment of the present invention, the nanocore material is preferably a metal organic framework nanoparticle or a metal organic framework nanosheet.
[0013] According to an embodiment of the present invention, the metal organic framework nanoparticles or metal organic framework nanosheets can be made of metal organic framework materials known in the art, for example, selected from ZIF-8, HKUST-1, UiO-66, and MOF-5.
[0014] According to an embodiment of the present invention, in step 1, the first solvent is selected from water and / or a polar solvent. Preferably, the polar solvent is selected from at least one of ethanol, methanol, dimethylformamide (DMF), dichloromethane (DCM), ethyl acetate, and chloroform.
[0015] According to an embodiment of the present invention, in step 1, the second solvent is selected from water and / or a polar solvent, and the polar solvent is miscible with water.
[0016] According to an embodiment of the present invention, in step 1, the first solvent and the second solvent may be the same or different, and are independently selected from water and / or polar solvents, and the polar solvent has the meaning as described above. Exemplarily, when the nanocore material is selected from metal organic framework nanoparticles or metal organic framework nanosheets, the first solvent is selected from polar solvents (such as methanol, ethanol), and the second solvent is selected from water. For example, ethanol and water are mixed in a volume ratio of 1:9 to obtain a 10% ethanol aqueous solution, and its freezing point is about -4.5°C; for example, ethanol and water are mixed in a volume ratio of 2:8 to obtain a 20% ethanol aqueous solution, and its freezing point is about -8 to -9°C.
[0017] According to an embodiment of the present invention, in step 2, the quenching refers to rapid cooling at a temperature lower than the annealing temperature (such as -30°C) to obtain solvent crystals, and liquid nitrogen or a -80°C low-temperature refrigerator can be commonly used.
[0018] According to an embodiment of the present invention, in step 2, the quenching can be performed in a manner known in the art, such as in liquid nitrogen or a low-temperature refrigerator.
[0019] According to an embodiment of the present invention, in step 2, the dispersion of the nano-core material and the dispersion of the nano-sheet material are mixed in a manner selected from the first or second manner:
[0020] Method 1: quickly blending the dispersion of the nano-core material and the dispersion of the nano-sheet material, and then quenching to form the solvent crystals;
[0021] Method 2: Alternately drop the dispersion of the nanocore material and the dispersion of the nanosheet material into a low temperature environment (lower than the freezing point of the solvent, such as -60°C for the 10% ethanol aqueous solution), and then quench to form the solvent crystals.
[0022] According to an embodiment of the present invention, in step 2, in the solvent crystal, the molar ratio of the nano-sheet material to the nano-core material is (2-3):1, preferably 2:1.
[0023] According to an embodiment of the present invention, in step 2, the concentration of the nanocore material in the solvent crystal is not specifically limited as long as a nano sandwich structure can be prepared, for example, 0.01 mg / ml-0.1 mg / ml.
[0024] According to an embodiment of the present invention, in step 2, in the solvent crystal, the size of the nano-sheet material is not less than the size of the nano-core material. Preferably, the size of the nano-sheet material is 1 to 2 times the size of the nano-core material.
[0025] According to an embodiment of the present invention, in step 3, during the aging process, the solvent crystals are recrystallized, that is, the smaller solvent crystals are dissolved and deposited again on the larger solvent crystals, and the confined space exists on the surface of the solvent crystals. As the recrystallization continues, the concentration of the nano-sheet material and the nano-core material in the confined space and / or on the surface of the solvent crystals gradually increases, and the nano-sandwich structure is obtained by precise assembly.
[0026] According to an embodiment of the present invention, in step 3, the conditions of the annealing treatment include: constant temperature annealing for a period of time at an annealing temperature. Preferably, the annealing temperature does not exceed the solidification point T of the mixed solution, preferably 5 to 30°C lower than the solidification point T of the mixed solution; illustratively, the annealing temperature is between T-5°C and T-30°C, for example, T-10°C, T-20°C. Preferably, the annealing time is 45 minutes to 120 minutes, for example, 60 minutes, 90 minutes, 120 minutes. In the present invention, the solidification point of the mixed solution refers to the solidification point after the first solvent and the second solvent are mixed. In the present invention, the higher the annealing temperature, the faster the ripening of the solvent crystals, and the shorter the required annealing time. In the present invention, the nano-core material and the nano-sheet material are precisely assembled in the confined space provided by the solvent crystal and / or on the surface of the solvent crystal. By simply controlling the appropriate annealing temperature, the mixed crystal can be prevented from ripening too fast, thereby avoiding the aggregation of the nano-sheet material and / or the nano-core material.
[0027] According to an embodiment of the present invention, in step 3, the annealing treatment can be carried out under conditions known in the art, such as in a refrigerator or a cold storage.
[0028] According to an embodiment of the present invention, the preparation method further comprises: Step 4: further removing the solvent crystals to obtain the nano sandwich structure.
[0029] According to an embodiment of the present invention, in step 4, removing the solvent crystals is specifically drying.
[0030] According to a preferred embodiment of the present invention, the drying may be carried out by a drying method known in the art, such as at least one or more selected from atmospheric pressure drying, reduced pressure drying, freeze drying or supercritical drying.
[0031] According to an embodiment of the present invention, in step 4, solvent replacement may be performed first to obtain solvent crystals that are easier to remove, and then the solvent crystals may be removed by the above-mentioned drying method or the like.
[0032] According to an exemplary embodiment of the present invention, the method for preparing the nano sandwich structure includes:
[0033] S1: Selecting 0.5 μm nanosheet materials (such as graphene oxide nanosheets) and 0.5 μm nanocore materials (such as metal organic framework particles), dispersing the nanocore materials in ethanol to obtain a dispersion of 0.1 mg / ml nanocore materials; dispersing the nanosheet materials in water to obtain a dispersion of 5 wt% nanosheet materials, and the volume ratio of ethanol to water is 1:9;
[0034] S2: Alternately dropping the dispersion of the nano-core material and the dispersion of the nano-sheet material in S1 in a low-temperature environment by means of micro-droplets, and quenching to form mixed solvent crystals;
[0035] S3: raising the temperature to -20°C and annealing for 45 minutes, so that the mixed solvent crystals are ripened, the nano-sheet materials and the nano-core materials are dispersed in the confined space on the surface of the mixed solvent crystals, and the nano-sandwich structure is precisely assembled in the confined space and / or on the surface of the solvent crystals;
[0036] S4: The mixed solvent crystals are removed by freeze drying to obtain a monodisperse nano-sandwich structure.
[0037] The present invention also provides a nano sandwich structure, which includes a nano sheet material and a nano core material, wherein the nano sheet material is precisely assembled on the outer surface of the nano core material at the nano scale; and the size of the nano sheet material is not less than the size of the nano core material.
[0038] Preferably, the nano-core material is precisely assembled between two nano-sheet materials, and the two nano-sheet materials are precisely assembled on the outer surface of the nano-core material at the nanoscale to form the nano-sandwich structure.
[0039] According to an embodiment of the present invention, the nano sandwich structure comprises at least two nano sheet materials and one nano core material, and the two nano sheet materials completely or partially wrap the outer surface of the nano core material.
[0040] According to an embodiment of the present invention, in the nano sandwich structure, the nano sheet material is a solvent-dispersed sheet material.
[0041] According to an embodiment of the present invention, the sheet material is selected from graphene oxide nanosheets, graphene nanosheets, graphyne nanosheets, MXene and other flexible nanosheet materials.
[0042] According to an embodiment of the present invention, the size of the nano-sheet material is 1-2 times, for example, 1 time or 1.5 times, the size of the nano-core material.
[0043] According to an embodiment of the present invention, the size of the nano-platelet material is not greater than 5 μm, for example, 0.1-5 μm, and for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm.
[0044] According to an embodiment of the present invention, the sheet-like material may be a single-layer and / or few-layer structure.
[0045] According to an embodiment of the present invention, the nanocore material has the meaning as described above, for example, a nanoparticle structure and / or a nanoplatelet structure.
[0046] According to an embodiment of the present invention, the nanocore material is selected from nanoparticles, nanosheets, molecular sieves, and the like.
[0047] According to an embodiment of the present invention, the size of the nano-core material is not greater than 3 μm, preferably 0.1-3 μm, for example 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 3 μm. When the size is greater than 3 μm, the particles or nano-sheets of the nano-core material are easily precipitated.
[0048] According to an embodiment of the present invention, the nanocore material is preferably a metal organic framework nanoparticle or a metal organic framework nanosheet.
[0049] According to an embodiment of the present invention, the metal organic framework nanoparticles or metal organic framework nanosheets can be made of metal organic framework materials known in the art, for example, selected from ZIF-8, HKUST-1, UiO-66, and MOF-5.
[0050] According to an embodiment of the present invention, the nano-sheet material is combined with the nano-core material by using hydrophilic and hydrophobic and / or electrostatic interactions as driving forces.
[0051] According to an embodiment of the present invention, the molar ratio of the nano-sheet material to the nano-core material is (2-3):1, for example, 2.5:1, preferably 2:1.
[0052] According to an embodiment of the present invention, the precise assembly refers to assembly by confined freezing on the surface of a solvent crystal, specifically comprising: firstly, rapidly mixing a dispersion of a nano-core material and a dispersion of a nano-sheet material, and then quenching to form a solvent crystal, in which the nano-sheet material and the nano-core material are dispersed; and then the solvent crystal is annealed, and since the solute is enriched at the interface of the solvent crystal, a confined space is formed on the surface of the solvent crystal, and the nano-core material and the nano-sheet material are precisely assembled on the nanoscale in the confined space and / or on the surface of the solvent crystal, and the nano-core material is wrapped between two nano-sheet materials to obtain the nano sandwich structure.
[0053] According to an embodiment of the present invention, the dispersion liquid of the nano-core material and the dispersion liquid of the nano-sheet material contain at least a solvent, and the solvent is quenched to form solvent crystals.
[0054] According to an embodiment of the present invention, the solvent is selected from water and / or a polar solvent. Preferably, the polar solvent is selected from a polar solvent miscible with water. Preferably, the polar solvent is, for example, selected from at least one of ethanol, methanol, dimethylformamide (DMF), dichloromethane (DCM), ethyl acetate, and chloroform.
[0055] In the present invention, a polar solvent is selected, and the surface of the solvent crystal formed by the solvent crystal has a preferential adsorption on the nano-sheet material. Therefore, in the process of confined freezing assembly, the nano-sheet material is first adsorbed on the surface of the solvent crystal, and the core material is driven by hydrophilic and hydrophobic and / or electrostatic effects to combine with the nano-sheet material to achieve precise assembly, and the solvent crystal plays a template role. In the present invention, by adjusting the initial concentration of the nano-sheet material and the nano-core material and the confined effect of the solvent crystal, the aggregation phenomenon of the nano-sheet material or the nano-core material is effectively avoided.
[0056] According to an embodiment of the present invention, the shape of the nano-core material is, for example, at least one selected from a polyhedron, a sheet, and a multilayer structure.
[0057] According to an embodiment of the present invention, the nano sandwich structure is a monodisperse particle. In the present invention, the monodisperse particle refers to a nanoparticle or a nanosheet material that can achieve single dispersion at the nanoscale.
[0058] According to an embodiment of the present invention, the nanomaterial has better fluidity, fillability and specific surface area.
[0059] According to an embodiment of the present invention, the nano sandwich structure is prepared by the above-mentioned method for preparing a nano sandwich structure.
[0060] The present invention also provides applications of the nano sandwich structure, for example, in the fields of gas adsorption and / or separation, catalysis (such as photodegradation), energy storage, sensing and drug delivery.
[0061] According to an embodiment of the present invention, in the nano sandwich structure, when the nano core material is selected from a metal organic framework with photodegradation performance, the nano sandwich structure photodegrades organic pollutants under visible light irradiation.
[0062] According to an embodiment of the present invention, in the nano sandwich structure, when the nano sheet material is selected from graphene oxide, which has excellent film forming properties and electrical properties, the nano sandwich structure can form a film and provide a customized diffusion path for molecules in the film.
[0063] Beneficial Effects
[0064] 1. The present invention obtains a nano sandwich structure by a confined freezing assembly method, which has broad application potential in the fields of separation, catalysis, sensing, etc.
[0065] 2. The preparation method of the nano sandwich structure of the present invention has the following advantages:
[0066] 1) It has wide applicability to different types of nanomaterials and materials, such as MOF systems;
[0067] 2) The nano sandwich structure of the present invention has strong dimensional adjustability and can be applied to different application scenarios;
[0068] 3) The method of the present invention is applicable to a system of various nano-sheet materials or nano-core materials, thereby obtaining nano-sandwich structures with various shapes and functions such as polyhedral, sheet-like, and multi-layer structures;
[0069] 4) Compared with traditional composite materials, the present invention can achieve precise assembly at the nanoscale to obtain a monodisperse nano sandwich structure with better fluidity, fillability and specific surface area, which helps to improve efficiency in applications such as catalysis and adsorption;
[0070] 5) The method of confined freezing assembly adopted by the present invention can not only accurately control the assembly process of nano-sheet materials and nano-core materials, but also maximize the advantages of the two nano-materials while improving the performance of the nano-sandwich structure, and the prepared nano-sandwich structure has higher stability. This simple method has low cost and has unique advantages for the development of new nano-functional materials.
[0071] 6) Compared with the liquid phase preparation process, the present invention utilizes the confinement effect of the solvent crystals between the solvent crystals, and achieves precise assembly of the nano sandwich structure by adjusting the initial concentration and the temperature and time of recrystallization. The nano sheet material is preferentially adsorbed on the surface of the solvent crystal, and by controlling the annealing temperature and time, the nano sheet core material is gradually enriched in the confined space and / or on the surface of the solvent crystal. Through hydrophilic and / or electrostatic effects, the nano sheet material and the nano core material are precisely assembled, thereby obtaining the nano sandwich structure of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 This is a scanning electron microscope (SEM) image of the MOF-GO nano-sandwich structure;
[0073] Figure 2 Transmission electron microscope (TEM) image of MOF-GO nano sandwich structure;
[0074] Figure 3 This is a 3D reconstruction image of a single particle of a MOF-GO nano-sandwich structure using cryo-electron microscopy;
[0075] Figure 4 Powder X-ray diffraction of MOF-GO nano sandwich structure;
[0076] Figure 5 This is the BET adsorption-desorption curve of MOF-GO nano sandwich structure. DETAILED DESCRIPTION
[0077] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0078] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0079] Example 1
[0080] The preparation process of ZIF-8-GO nano sandwich structure is as follows:
[0081] Step 1: Disperse 0.1 mg / ml ZIF-8 with an average size of about 0.5 μm in ethanol to obtain a MOF dispersion; disperse 5 wt% GO with an average size of 0.5 μm in water to obtain a GO dispersion; wherein the volume ratio of ethanol to water is 1:9;
[0082] Step 2: Alternately drop the above two dispersions into a low-temperature container at -80°C by microdroplet method for low-temperature quenching to form fine mixed solvent crystals, in which GO and ZIF-8 are dispersed;
[0083] Step 3: Raise the temperature in the cryogenic container to -20°C for annealing for 45 minutes to ripen the finely divided mixed solvent crystals. During the ripening process, the smaller solvent crystals dissolve and deposit again on the larger solvent crystals. As the solute is enriched at the interface, a confined space is formed on the surface of the mixed solvent crystals. The concentrations of GO and ZIF-8 in the confined space increase, and GO and ZIF-8 are assembled in the confined space of the solvent crystals and / or on the surface of the solvent crystals to obtain a nano sandwich structure.
[0084] Step 4: The solvent crystals in the above system are removed by freeze-drying to obtain a monodispersed ZIF-8-GO nano-sandwich structure.
[0085] Figure 1 This is a scanning electron microscope (SEM) image of the ZIF-8-GO nanosandwich structure; Figure 2 Transmission electron microscopy (TEM) image of ZIF-8-GO nanosandwich structure; Figure 3 This is a three-dimensional reconstruction image of a single particle of a ZIF-8-GO nanosandwich structure using cryo-electron microscopy. Figure 1-3 It can be seen that the average size of the ZIF-8-GO nano sandwich structure prepared in this example is 0.5 μm, and in the ZIF-8-GO nano sandwich structure, ZIF-8 is coated between two GO nanosheets to form a monodisperse sandwich structure.
[0086] Figure 4 The powder X-ray diffraction pattern of the ZIF-8-GO nanosandwich structure is shown in Figure 2. Figure 4 It can be seen that the MOF-GO nano-sandwich structure prepared in this embodiment is basically consistent with the diffraction pattern of ZIF-8. It can be seen that the MOF-GO nano-sandwich structure prepared in this embodiment hardly affects the original crystal properties of ZIF-8.
[0087] Application Example 1
[0088] Application of the ZIF-8-GO nano sandwich structure of Example 1 in gas adsorption
[0089] Take 100 mg of the ZIF-8-GO nano sandwich structure of Example 1 as a sample, activate it under high vacuum (10-6 bar) at 393 K for 6 hours, and put the sample into a sample tube to test the N2 adsorption isotherm. Figure 5 As shown. Figure 5 It can be seen that compared with pure ZIF-8, the N2 adsorption capacity of the ZIF-8-GO nano sandwich structure of the present invention not only did not decrease, but increased by 5% to 10%. Figure 4 The XRD data show that the ZIF-8-GO nano sandwich structure of the present invention retains the function of ZIF-8 and significantly improves its stability.
[0090] It can be seen that the ZIF-8-GO nano sandwich structure of the present invention has broad application potential in the fields of gas separation and catalysis.
[0091] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a nano sandwich structure, characterized in that: The preparation method comprises: Step 1: dispersing the nano-core material in a first solvent to obtain a dispersion of the nano-core material, and dispersing the nano-sheet material in a second solvent to obtain a dispersion of the nano-sheet material; Step 2: mixing the dispersion of the nano-sheet material and the dispersion of the nano-core material in step 1 to obtain a mixed solution, and quenching to form solvent crystals; the nano-sheet material and the nano-core material are dispersed in the solvent crystals; Step 3: Annealing the solvent crystals obtained in step 2 to mature the solvent crystals; at this time, due to the enrichment of the solute at the interface, a confined space is formed on the surface of the solvent crystal, and the nano-sheet material and the nano-core material are dispersed in the confined space, achieving precise assembly on the nanoscale to obtain the nano-sandwich structure.
2. The preparation method according to claim 1, characterized in that: In step 1, the nanocore material is a nanoparticle structure and / or a nanosheet structure. Preferably, the nanocore material is selected from at least one of nanoparticles, nanosheets and molecular sieves. Preferably, the size of the nano-core material is no greater than 3 μm. Preferably, the nanocore material is metal organic framework nanoparticles or metal organic framework nanosheets. Preferably, in step 1, the first solvent is selected from water and / or a polar solvent. Preferably, the polar solvent is selected from at least one of ethanol, methanol, dimethylformamide, dichloromethane, ethyl acetate and chloroform. Preferably, in step 1, the second solvent is selected from water and / or a polar solvent, and the polar solvent is miscible with water. Preferably, in step 1, the first solvent and the second solvent may be the same or different and are independently selected from water and / or polar solvents.
3. The preparation method according to claim 1 or 2, characterized in that: In step 2, the quenching is to obtain solvent crystals by rapid cooling. Preferably, in step 2, the method of mixing the dispersion of the nano-core material and the dispersion of the nano-sheet material can be selected from method 1 or method 2: Method 1: quickly blending the dispersion of the nano-core material and the dispersion of the nano-sheet material, and then quenching to form the solvent crystals; Method 2: Alternately dropping the dispersion of the nano-core material and the dispersion of the nano-sheet material into a low-temperature environment in the form of droplets, and then quenching to form the solvent crystals. Preferably, in step 2, in the solvent crystals, the molar ratio of the nano-sheet material to the nano-core material is (2-3):
1. Preferably, in step 2, in the solvent crystal, the size of the nano-sheet material is not less than the size of the nano-core material. Preferably, the size of the nano-sheet material is 1 to 2 times the size of the nano-core material.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step 3, during the aging process, the solvent crystals are recrystallized, that is, the smaller solvent crystals are dissolved and deposited again on the larger solvent crystals, and the confined space exists on the surface of the solvent crystals. Preferably, in step 3, the annealing treatment conditions include: constant temperature annealing for a period of time at an annealing temperature. Preferably, the annealing temperature does not exceed the freezing point T of the mixed solution. Preferably, the preparation method further comprises: step 4: further removing the solvent crystals to obtain the nano sandwich structure.
5. A nano sandwich structure, characterized in that: The nano sandwich structure comprises a nano sheet material and a nano core material, wherein the nano sheet material is precisely assembled on the outer surface of the nano core material at the nano scale; and the size of the nano sheet material is not less than the size of the nano core material.
6. The nano sandwich structure according to claim 5, characterized in that: The nano-core material is precisely assembled between two nano-sheet materials, and the two nano-sheet materials are precisely assembled on the outer surface of the nano-core material at the nanoscale to form the nano-sandwich structure. Preferably, the nano sandwich structure comprises at least two nano sheet materials and one nano core material, and the two nano sheet materials completely or partially wrap the outer surface of the nano core material.
7. The nano sandwich structure according to claim 5 or 6, characterized in that: In the nano sandwich structure, the nano sheet material is a sheet material that can be dispersed in a solvent. Preferably, the sheet material is selected from flexible nanosheet materials such as graphene oxide nanosheets, graphene nanosheets, graphyne nanosheets, and MXene. Preferably, the size of the nano-sheet material is 1-2 times the size of the nano-core material. Preferably, the size of the nano-sheet material is not greater than 5 μm. Preferably, the sheet material is a single-layer and / or few-layer structure.
8. The nano sandwich structure according to any one of claims 5 to 7, characterized in that: The nanocore material is selected from at least one of nanoparticles, nanosheets, and molecular sieves. Preferably, the size of the nano-core material is no greater than 3 μm. Preferably, the nanocore material is metal organic framework nanoparticles or metal organic framework nanosheets. Preferably, the nano-sheet material is combined with the nano-core material by using hydrophilic and hydrophobic and / or electrostatic interactions as driving forces. Preferably, the molar ratio of the nano-sheet material to the nano-core material is (2-3):
1. Preferably, the precise assembly refers to assembly by confined freezing on the surface of a solvent crystal.
9. The nano sandwich structure according to any one of claims 5 to 8, characterized in that: The shape of the nano-core material is selected from at least one of a polyhedron, a sheet, and a multi-layer structure. Preferably, the nano sandwich structure is monodisperse particles. Preferably, the nanomaterial has better fluidity, fillability and specific surface area.
10. Application of the nano sandwich structure according to any one of claims 5 to 9 in the fields of gas adsorption and / or separation, catalysis, energy storage, sensing and drug delivery.